Varieties Of Anaphora - Ibragimova Odinakhon (International Journal on Human-Computing Studies, 2022)
This article discusses varieties of anaphora. Anaphora has been identified with a limited set of words, but in the past decades there have been many proposals to interpret other phenomena as anaphora. While most people would agree that these phenomena are context-dependent, the claim that they belong to one and the same class, namely anaphora is much more controversial.